THE EFFECT OF SOCIAL MEDIA ON MARKETING - Emine ARSLAN (International Journal of Eurasia Social Sciences, 2017)
Thanks to advancements in Web 2.0. technology, social networks have emerged. Businesses that care about social media advertise their products to customers through social media. From the perspective of businesses, how social media tools shape marketing is of importance. Businesses which meet current and potential customers’ requests and needs use social media to promote their products after producing them. The effects of social media on university students with respect to marketing are aimed to be identified in this study. The data obtained from the questionnaires were analyzed via SPSS 22.0 statistical package program. According to the research results, social media effects purchasing behavior of university students.